Vaccination coverage of triple viral and poliomyelitis in Brazil, 2011-2021: temporal trend and spatial dependency - Isadora Gabriella Silva Palmieri; Lucas Vinícius de Lima; Gabriel Pavinati; José Arthur Paschoalotto Silva; Sonia Silva Marcon; Ana Paula Sayuri Sato; Gabriela Tavares Magnabosco (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To analyze the coverage of MMR and polio vaccines, the temporal trend and spatial dependence, in children up to one year of age in Brazil, between 2011 and 2021. Methods: Ecological study with secondary data on vaccination coverage rates, made available by the National Immunization Program Information System. Trend analysis was carried out using the joinpoint method, according to geographic regions, estimating the annual percentage change (APC) and its respective confidence interval (95%CI). Choropleth maps of distribution by health region were constructed and, subsequently, the spatial dependence was verified using Moran's statistics. Results: Between 2011 and 2021, vaccination coverage declined in Brazil, both for MMR (APC: −6.4%; 95%CI −9.0; −3.8) and for poliomyelitis (APC: −4. 5%; 95%CI −5.5; −3.6). There was a decline in coverage of both vaccines in all geographic regions over the years of the study, except in the South and Midwest for the MMR vaccine. Since 2015, few health regions in the country have achieved adequate vaccination coverage (≥95.0% to <120.0%). The North and Northeast health regions showed low-low clusters in the univariate analysis for both immunobiological. Conclusions: It is urgent to consider studies like this one for the planning of more effective strategies for immunizing children, especially in areas with higher falls. In this way, barriers to access to immunization can be broken, given Brazil's heterogeneity, and access to reliable information that increases confidence in vaccine efficacy can be expanded.